2022
DOI: 10.1111/ppc.13081
|View full text |Cite
|
Sign up to set email alerts
|

The effects of family function, relationship satisfaction, and dyadic adjustment on postpartum depression

Abstract: Purpose: To determine the effect of family function, relationship satisfaction, and dyadic adjustment on postpartum depression Design and Methods: This descriptive, cross-sectional study was conducted in 337 postpartum mothers. Findings: Fifty-five mothers scored above the depression scale cutoff point (>13). Emotional violence from husband, poor problem solving and communication, low relationship satisfaction, dyadic adjustment, and consensus were important risk factors for postpartum depression (p < .0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…And, the nding still showed that postnatal women who have better marital adjustment were less likely to diagnose PPD, which consistent with prior study [17], good marital quality could hand women more power to face the challenges of postpartum period [50]. Additionally, a Meta-Analysis consisted of 84 studies[18] found marital status as a predictor of PPD, maternal mental well-being with poor dyadic adjustment would be deteriorated [17,49]. In this study, 30% of participants reported maladaptation in marital, with the transition to parenthood, many couples may feel overwhelmed by many new responsibilities and demands, spend less time together, make increase in marital con ict, thereby reducing relationship satisfaction, which has been identi ed as a relatively strong risk factor for PPD [50][51][52].…”
Section: Discussionsupporting
confidence: 72%
“…And, the nding still showed that postnatal women who have better marital adjustment were less likely to diagnose PPD, which consistent with prior study [17], good marital quality could hand women more power to face the challenges of postpartum period [50]. Additionally, a Meta-Analysis consisted of 84 studies[18] found marital status as a predictor of PPD, maternal mental well-being with poor dyadic adjustment would be deteriorated [17,49]. In this study, 30% of participants reported maladaptation in marital, with the transition to parenthood, many couples may feel overwhelmed by many new responsibilities and demands, spend less time together, make increase in marital con ict, thereby reducing relationship satisfaction, which has been identi ed as a relatively strong risk factor for PPD [50][51][52].…”
Section: Discussionsupporting
confidence: 72%
“…Our findings suggest the accumulative mediating role of depression and self-perceived burden in the family function and loneliness. Many previous studies have shown that good family function can help improve the mental health of patients with T2DM [ 30 , 31 ]. Good family function can enhance the psychological elasticity of patients and inhibit the generation of negative emotions, and hence, reduce their depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings suggest the accumulative mediating role of depression and self-perceived burden in the family function and loneliness. Many previous studies have shown that good family function can help improve the mental health of patients with T2DM [30,31]. Good family function can enhance the psychological elasticity of patients and inhibit the generation of negative emotions, and hence, reduce their depression.…”
Section: Chain Mediating Effect Of Depression Self-perceived Burden I...mentioning
confidence: 99%
“…A longitudinal study conducted by Zhou et al [29] demonstrated that low self-esteem affected depression in adolescents, partly through the mediating effect of loneliness. Good family function can effectively reduce the occurrence or level of depression in postpartum women [30,31], the elderly [32], and epileptic children [33]. Some studies have also reported that in T2DM patients, good family function can enhance the psychological elasticity of patients, inhibit the generation of negative emotions such as anxiety and depression symptoms, and help regulate the blood glucose uctuations [26].…”
mentioning
confidence: 99%